Clinical Characteristics of Pruritus in Systemic Sclerosis Vary According to the Autoimmune Subtype - Greta Gourier; Chloé Théréné; Margaux Mazeas; Claire Abasq-Thomas; Emilie Brenaut; Flavien Huet; Haitham Sonbol; Elize Campillo; Julie Lemerle; Elisabeth Pasquier; Emmanuelle Le Moigne; Alain Saraux; et al. (Medical Journals Sweden, 2018)
Pruritus is a frequent symptom in systemic sclerosis (SSc), with a prevalence of 40-65%, but its pathophysiology is poorly understood. This study investigated the immunological component of pruritus. Fifty-six patients with SSc responded to a standardized questionnaire regarding both SSc disease and pruritus characteristics. Among patients with SSc, those with pruritus did not display a particular immunological profile (inflammatory, humoral, and/or cellular factors), but pruritus was, in most cases, concomitant with the development of SSc. Thus, pruritus characteristics were evaluated further, according to the detection of anti-centromere autoantibodies (ACA), into ACA+ (n = 17) and ACA- (n = 19). The ACA+ subgroup was characterized by a longer evolution of SSc and pruritus, pruritus present outside the sclerotic area, and a shorter daily duration of pruritus. In conclusion, the concomitant appearance of the 2 processes and the differences observed between ACA+ and ACA- subgroups support the presence of an immunological component in pruritus.